Vaccination strategies for a foot-and-mouth disease outbreak in southwest Kansas - Greathouse, Brian Dean, author; Pendell, Dustin L., advisor; Hill, Ashley E., committee member; Seitzinger, Ann Hillberg, committee member; Thilmany McFadden, Dawn, committee member (Colorado State University. Libraries, 2010)
Globalization has expanded market opportunities for U.S. livestock producers. With the increase in world travel and globalization of agriculture, the possibility of transmitting a highly contagious foreign animal disease to the U.S. is higher. Therefore, it is critically important to develop and assess economic implications of emergency management plans in the event a contagious livestock disease outbreak was to occur in the U.S. For example, the United Kingdom experienced a severe FMD outbreak in 2001. By the end of the outbreak, 221 days after it started, 2,026 cases of FMD had been confirmed, over six million animals were destroyed, and the disease had spread to Ireland, France, and the Netherlands. Thompson et al. (2002) estimated losses from FMD in the UK at £5.8 to £6.3 billion ($8.47 to $9.20 billion U.S.). Responding to public opposition in the UK to the eradication measures, as well as the demand for an alternative destruction approach because of limited carcass disposal due to concerns about water (burial) or air pollution by smoke (burning), the USDA's Animal and Plant Health Inspection Service (APHIS) - Veterinary Service (VS) recently unveiled its vision for the future called VS 2015. According to APHIS (2009), VS 2015 "will allow the organization to place greater emphasis on disease prevention, preparedness, detection and early response activities" (page 1). There are several forces driving this initiative and its focus: diseases that were once eradicated or controlled are beginning to emerge again, changes in the industry structure (an increase in the number of large-scale, production-intensive operations), advances in technology, public awareness of diseases, demand for protein (especially in developing countries), and shrinking federal budgets (which has an increased emphasis on optimal allocation of resources). Combining APHIS's VS 2015 vision and the recent advances in FMD vaccines, it is imperative that policies are developed with input from both the epidemiological and economic sciences. The purpose of this study is to estimate the epidemiological and economic impacts associated with the various emergency vaccination strategies in the event of a FMD outbreak in a large cattle feeding region, where large-scale depopulation activities might not be feasible. In this study, we will compare the impacts of using vaccination as a way to control the spread of FMD on the time of detection and across herd size. Additionally, we investigate the changes in producer and consumer welfare associated with: the optimal timeframe in which officials have to begin the vaccination strategy; and destruction or alternative marketing channels for vaccinated animals (i.e., what happens if all vaccinated animals are destroyed vs. if the vaccinated animals are not destroyed.) To achieve the objectives of this study, a stochastic epidemiological disease spread model is used to simulate a hypothetical FMD outbreak outside of this thesis. Results from the disease spread model are then incorporated into an equilibrium displacement model (EDM). The EMD is a set of supply and demand equations that incorporates multiple commodities, multiple marketing levels within the farm-retail marketing chain, and international trade. The results obtained from the epidemiological model indicate that varying the number of herds detected before vaccination commenced had a minor impact on the number of animals destroyed, number of animals vaccinated and the length of the outbreak. The economic results suggest that no vaccination has the smallest decline in producer welfare when compared to the vaccination scenarios. Varying the number of herds detected before vaccination begins has little impact on producer and consumer welfare. When destroying the vaccinated animals, the impacts are larger at the producer levels compared to the scenarios when animals are not destroyed. As would be expected, when the export markets are closed longer, the impacts are larger. The various scenarios studied suggest the total producer meat surplus decreases between $15,810.6 and $21,324.9 million. The total consumer meat surplus decreases $2,581.8 and $5,875.6 million.
Department Head: Stephen P. Davies.